1994
DOI: 10.1177/0032855594074004003
|View full text |Cite
|
Sign up to set email alerts
|

Functional Literacy Education for Jail Inmates: An Examination of the Hillsborough County Jail Education Program

Abstract: Offenders incarcerated in jails in Hillsborough County, Florida, had the opportunity to participate in an education program using computer-assisted instruction for basic literacy education and GED preparation. Although literacy levels were low with a tested mean of sixth grade prior to entering the program, participants made statistically significant gains in knowledge during 6 weeks of instruction. Overall, participants gained 2.40 grades during this period. Significance tests based on gender, race, and age w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Demographic measures included age, race and sex. These three variables have been shown in several other studies as significant correlates of illicit activities (Sampson and Laub 1993;Steffensmeier and Streifel 1991), as well as predictors of outcomes in some treatment modalities (Smith and Silverman 1994). Thus, these measures are examined in the bivariate and the multivariate models.…”
Section: Independent Measuresmentioning
confidence: 96%
“…Demographic measures included age, race and sex. These three variables have been shown in several other studies as significant correlates of illicit activities (Sampson and Laub 1993;Steffensmeier and Streifel 1991), as well as predictors of outcomes in some treatment modalities (Smith and Silverman 1994). Thus, these measures are examined in the bivariate and the multivariate models.…”
Section: Independent Measuresmentioning
confidence: 96%
“…As shown above, these were integral strategies that slaves relied on. In addition, some research has shown that African Americans gain more from prison educational programs than whites (e.g., [79]. Unfortunately, Adams ([1]:291) notes that there is a shortage of research concerning "successful" coping in prisons.…”
Section: Gst Applied To Prisonmentioning
confidence: 99%
“…The education needed by these people is hopefully will also build their character as it is for their knowledge. The previous research [5] stated that functional literacy program implied on jail inmates is aimed to decrease the criminality.…”
Section: Introductionmentioning
confidence: 99%